First inventory of vascular flora of Matokit mountain (Biokovo massif, Croatia) : Prva inventarizacija vaskularne flore planine Matokit (Biokovo masiv, Hrvatska) - Vitasović Kosić, Ivana (Array, 2020)
The vascular flora of Matokit Mt (Biokovo Massif) in southern Croatia was researched in different vegetation periods from 2010-2015, and a total of 604 vascular plant taxa belonging to 86 families and 337 genera were found. The studied area has never been studied in the past and these are the first detailed floristic data about grasslands in different succession stages of Matokit Mt. Collected herbarium specimens (345 sheets) were digitalized and are available at the ZAGR Virtual Herbarium. The most dominant families were legumes (Fabaceae 9.9%), grasses (Poaceae 9.1%), daisies (Asteraceae 7.4%) and mints (Lamiaceae 6.8%). The analysis of life forms shows the dominance of hemicryptophytes (39.9%) and therophytes (26.2%) on Matokit Mt that indicates a high influence of the Mediterranean climate. A total of 36 endangered and 17 invasive plant taxa across the whole studied area were recorded. Endemic are 32 plant taxa (26 endemics in a broader sense and 6 stenoendemics) and they represent new site of Croatian flora. The occurrence of some very rare endemics (Cardamine fialae Fritsch and Erysimum croaticum Polatschek) in the flora of Matokit Mt is of special interest for the national flora.